Analisis Kepemimpinan Pelayan, Perilaku Kerja Inovatif dan Kepuasan Kerja pada Badan Perencanaan Pembangunan Daerah dan Litbang-Kabupaten Kaur - Okno - Harianto; Slamat - Widodo; Paullus Sulluk Kananlua (Student Journal of Business and Management, 2021)
The research objectives were (1) to analyze the influence of servant leadership on employee job satisfaction, (2) to analyze the influence of leadership on employee innovative work behavior, (3) to analyze the influence of innovative work behavior on employee job satisfaction (4) to analyze the role of work behavior. innovative leadership in servant leadership of employee job satisfaction.  This research uses a quantitative approach with a survey method. The respondents were 82 employees at the Regional Development Planning and Research and Development Agency, Kaur Regency. They, namely employees and honorary. Data collection using online surveys and data analysis using path analysis and Sobel test. The results showed that servant leadership had a positive effect on job satisfaction. Servant leadership is positive for innovative work behavior. Innovative work behavior has a positive effect on job satisfaction. Innovative work behavior does not mediate the effect of servant leadership on job satisfaction of Bappeda and R & D employees of Kaur Regency. Keywords: Servant Leadership, Job Satisfaction, Innovative Work Behavior